BREAKING BARRIERS: A CRITICAL ANALYSIS OF MINDFULNESS-BASED PSYCHOTHERAPY'S ROLE IN DEMOCRATIZING MENTAL HEALTH SERVICES IN JAIPUR - Kashyap, Deepak; Jagawat, Savita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper examines the potential of mindfulness-based psychotherapy in democratizing mental health services in Jaipur, India. The study explores the current mental health landscape in Jaipur, identifies barriers to access, and analyzes how mindfulness-based interventions can address these challenges. Through a mixed-methods approach, including surveys, interviews, and case studies, the research investigates the efficacy, affordability, and cultural acceptability of mindfulness-based psychotherapy in the local context. The findings suggest that mindfulness-based approaches have significant potential to increase access to mental health services, reduce stigma, and improve overall mental well-being in Jaipur's diverse population. The paper concludes with recommendations for policymakers, mental health professionals, and community organizations to leverage mindfulness-based psychotherapy in democratizing mental health services.